PERANCANGAN STRUKTUR RANGKA LENGAN ROBOT MEKANIK PEMINDAH BAHAN TIPE CARTESIAN COORDINATE - Prayuda, Ilham Vega; Hartono, Budi; Sutoyo, Edi (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2018)
This study describes the design of skeletal structure of mechanical robot arm of cartesian coordinate material type with area of 60 x 50 cm using 2 main axis that is X axis and Y axis. This study aims to determine the movement system, frame construction, welded joints. Based on the design results, the driving force using the stepper motor OMHT17-275 for the driving force on the X axis that has a torque of 0.249 Nm, stepper motor OM5014-075 for the motor on Y axis which has a torque of 0.235 Nm. The stresses occurring in the lead screw are the compressive stress of 3.9 MPa, the bending stress of 0.028 MPa, and the shear stress of 3.3 MPa. The amount of stress that occurs in the lead screw is still below the yield strength of the material, so the lead screw is quite safe. Analyze on linear rod Y axis with S45C material get load 51,993 N caused stress 0,00245 MPa < material stres permit 29,419 MPa, and deflection 0,052 mm < software simulation result 0,072 mm, so material is considered safe. Analysis on linear rod X-axis with S45C material got 14,715 N caused stress 0.000721 MPa < material stres permit 29,419 MPa, and curve or buckling force on Y axis was 10,322 kg. The stress value that occurs < the stress of the material permit, therefore the design able to withstand the load occur. From the calculation of the tensile stress of 1.83 MPa < welding stress allowable 53.75 MPa, so the welding is considered safe. The shear stress value that occurs at 1.83 MPa < stress allowable 47.37 MPa, so the welding is considered safe.